Políticas públicas em educação para negros: a implementação da lei 10.639/03. - Silva, Izabel da (2009)
This dissertation addresses the Public Policies in the education of the black population in Brazil. Its overall objective is to analyze Law 10.639/03 as one of the Public Policies of Affirmative Action, which made compulsory the teaching of African and Afro-Brazilian History and Culture in all teaching establishments at the elementary school level.Specifically, this dissertation aims to research affirmative actions for blacks in the field of education and particularly analyzes the implementation process of the said law. the problems discussed refer to the difficulties in implementing this law in Brazil specifically in the state of Paraná. The theoretical reference of this work is placed in the perspective of historical materialism. Therefore, the analysis aims to relate the concept of social class with that of race and racism among other factors. This work was based mainly on works by the following researchers: Antonio Sergio Alfredo Guimarães, Carlos Hasenbalg, Florestan Fernandes, Fulvia Rosenberg, Henrique Cunha, Kabengele Munanga Otávio Ianni and Petronilla Beatriz Gonçalves e Silva, and others who have contributed to the knowledge of the theme. The methodology used is supported in the bibliographical analysis of official documents and interviews. The conclusion points out the limitations of the public policies in the implementation of the said law. One of the obstacles to such implementation is related to the lack of continuing education of teachers to enable them to work with Afro-Brazilian and African History and Culture so that they have the tools to engage in discussions and debates in the classroom. Moreover, it was observed that the implementation of the law did not happen mainly because of the racial prejudice which permeated the very fabric of school.